2010
DOI: 10.1088/0004-637x/710/1/16
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating the Correlation Between Black Hole Mass and X-Ray Variability Amplitude: X-Ray Only Black Hole Mass Estimates for Active Galactic Nuclei and Ultra-Luminous X-Ray Sources

Abstract: A calibration is made for the correlation between the X-ray Variability Amplitude (XVA) and black hole (BH) mass. The correlation for 21 reverberationmapped Active Galactic Nuclei (AGNs) appears very tight, with an intrinsic dispersion of 0.20 dex. The intrinsic dispersion of 0.27 dex can be obtained if BH masses are estimated from the stellar velocity dispersions. We further test the uncertainties of mass estimates from XVAs for objects which have been observed multiple times with good enough data quality. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
84
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 58 publications
16
84
2
Order By: Relevance
“…Previous studies have pointed out that the high-frequency PSD does not show a clear scaling with the luminosity/mass-accretion rate both in BHXRBs (Gierliński et al 2008) and AGN (O'Neil et al 2005;Zhou et al 2010;Ponti et al 2012). We observe that the high-frequency fractional rms of GX 339-4 is constant in the hard and very hard band (dominated by the hard X-ray Comptonization continuum) at any luminosity probed.…”
Section: The Scaling Of the High-frequency Psd With Luminosity In Bhxcontrasting
confidence: 43%
See 1 more Smart Citation
“…Previous studies have pointed out that the high-frequency PSD does not show a clear scaling with the luminosity/mass-accretion rate both in BHXRBs (Gierliński et al 2008) and AGN (O'Neil et al 2005;Zhou et al 2010;Ponti et al 2012). We observe that the high-frequency fractional rms of GX 339-4 is constant in the hard and very hard band (dominated by the hard X-ray Comptonization continuum) at any luminosity probed.…”
Section: The Scaling Of the High-frequency Psd With Luminosity In Bhxcontrasting
confidence: 43%
“…In analogy with BHXRBs, also in AGN the highfrequency PSD (above the high-frequency break) does not show any clear dependence on the luminosity/mass-accretion rate (e.g. O'Neil et al 2005;Zhou et al 2010;Ponti et al 2012). In this paper we aim at investigating the evolution of the PSD as a function of luminosity/mass-accretion rate, extending the analysis down to the soft X-ray energy band.…”
Section: Introductionmentioning
confidence: 97%
“…In fact the low bulge velocity dispersion (σ * < 30 km s −1 ; Filippenko & Ho 2003) deviates from the extrapolation of the M-σ relation when this estimate of the M BH is adopted (but see Greene & Ho 2006). The final Rev sample consists of 32 AGN (11 more AGN than in the Zhou et al 2010, sample), 6 of which are either absorbed or radio loud objects, hence they are not present in CAIXAvar.…”
Section: Reverberation Sample (Rev)mentioning
confidence: 95%
“…Miniutti et al (2009) confirmed the variability vs. M BH trend extending the variability estimation to smaller M BH AGN. Finally, Zhou et al (2010) tried to calibrate accurately, and estimate the intrinsic scatter of the σ 2 rms vs. M BH relation, using high quality XMM-Newton light curves of AGN with M BH measured through the "reverberation mapping" technique. They found that the intrinsic scatter of this relation is even smaller than the one implied by the M BH uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…M82 X-1's previous mass estimates of a few hundred solar masses combined with the Type-C identification 2,4,9 of its mHz X-ray quasi-periodic oscillations suggest that 3:2 ratio, twin-peak, high-frequency oscillations analogous to those seen in stellar-mass black holes, if present, should be detectable in the frequency range of a few Hz 16 . We accordingly searched Rossi X-ray Timing Explorer's (RXTE's) proportional counter array archival data to look for 3:2 oscillation pairs in the frequency range of [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Hz which corresponds to a black hole mass range of 50-2000 M ⊙ .…”
mentioning
confidence: 99%